Human Trafficking and Displacement in South Asia: An Econometric Analysis (Dhaka University Journal of Science, 2017)
Human trafficking has received increased media and national attention. Despite concerted efforts to combat human trafficking, the trade in persons persists and in fact continues to grow. This paper describes the relationship and distinction between trafficking and ethnic fragmentation, conflict, internally displaced person by different measures of control. To explain the relationship between these factors, this study uses a Probit regression model. It appears that ethnic conflict leads the internal displacement of individuals from networks of family and community, and their access to economic and social safety nets.Dhaka Univ. J. Sci. 65(1): 73-76, 2017 (January)